Exploring the potential of a school-based online health and wellbeing screening tool: professional stakeholders and young people's perspectives and experiences. (November 2021) - Woodrow, Nicholas; Fairbrother, Hannah; Breheny, Katie; d'Apice, Kartina; Albers, Patricia; Mills, Clare; Curtis, Matthew; Hopkins, Lisa; Tebbett, Sarah; Campbell, Rona; De Vocht, Frank
Abstract: Background: Supporting young people's mental and physical health is a global policy priority, but detecting need and facilitating access to health services and support is challenging. We aimed to explore the perspectives of young people and professional stakeholders of the acceptability, utility, and effectiveness of a school-based online health and wellbeing screening tool, the Digital Health Contact (DHC), which has linked follow-up support. The DHC was initially piloted in 2017, and has been running ever since. Methods: Delivered by Public Health School Nurses (PHSN) in the East Midlands, the DHC aims to identify and put in place strategies to meet the unmet health needs among young people. As part of a wider evaluation of the DHC intervention, we carried out semistructured online interviews. Data were analysed thematically. The data management software NVivo 12 was used to facilitate coding. Ethical approval for the study was granted by the University of Sheffield. Written informed consent was obtained from all participants. Findings: Between Aug 2, 2020, and June 8, 2021, we carried out online interviews with 14 key stakeholders involved in the design and implementation of the DHC (two commissioners, one provider, six PHSN, two health-care staff, and three school leaders; 13 female, one male) and 29 young people (aged 13–14 years old; 21 female, eight male) from one school who had participated in the DHC. Young people perceived the DHC as an acceptable and useful way of discussing health needs. The delivery method and context of the DHC (online, at home, and at school), and knowledge of the involvement of the PHSN in delivering the DHC, was noted by the young people to facilitate honest responses and greater amounts of engagement. Stakeholders perceived the universal application of the DHC with linked follow-up intervention as an effective means of identifying and supporting young people with unmet needs, and an efficient way to target limited service resources. There were barriers around enabling school engagement typically in terms of logistics, school infrastructure, and perspectives of fit with schools. These barriers were seen to be negated through developing effective working relationships between PHSN and schools. Interpretation: The DHC was consistently perceived as an effective and acceptable tool for detecting need and providing support from those delivering and receiving it. The DHC's universal screening and linked follow-up support approach has great potential and could be adopted more widely to help identify and support unmet health need among young people. Funding: This project is funded by the National Institute for Health Research School for Public Health Research (SPHR-PHPES009-DHC).